Sensitivity analysis and uncertainty quantification of stiffness modulus using indirect tensile test - Hicham Mezouara; Houcine Zniker; Ikram Feddal; Mohammed Khalil El Kouifat; Mohamed El Hasnaoui (International Journal of Applied Mechanics and Engineering)
The stiffness modulus is a critical element in pavement engineering, as its accurate measurement directly reflects the load-bearing capacity of the pavement section. Many researchers utilize indirect tensile tests in laboratory studies to determine this modulus. The pavement's performance, as well as other properties of the pavement layers, can be directly influenced by this modulus. It also provides insights into the resistance of the asphalt mix to permanent deformation due to repeated loads, a common issue in flexible pavements. The stiffness modulus holds a significant role in pavement and pavement materials-related works and designs. This research aims to address uncertainties in stiffness modulus measurements of asphalt mixtures, which can lead to unreliable results and poor decisions in pavement construction. The paper presents theoretical and experimental findings on the uncertainty and sensitivity analysis in identifying influential parameters in stiffness modulus measurement. Key factors such as experimental setup, interface roughness, sample shape, and plate-sample contact were evaluated for their impact on measurement uncertainty. The study found that test repeatability is the primary contributor to measurement error, accounting for approximately 79.72%, followed by thickness measurement, contributing around 19.75%.